Fabrication And Characterization Of Experimental Nanocomposites For Dental Restoration - Rahim, Tuan Noraihan Azila Tuan (2012)

(untitled)
Currently, restorative dental composites have become preferred among patients due to their aesthetic characteristic and also their durability. The high costs of composites, as well as the rising demand by patients have lead researchers to produce a local product with equivalent standard as compared to the commercially available dental composites. Recently, monodispersed, spherical silica nanofillers with a size range of 10-20 nm were successfully synthesized via a sol-gel process and have a great potential to be used in fabrication of dental composites.